The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fendo.2021.770400
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Glycated Hemoglobin in Frail Older Diabetic Patients With Hip Fracture

Abstract: BackgroundPrevious studies have shown increased risk of fracture in older patients with poor or strict glycemic control (glycated hemoglobin, HbA1c, ≥ 8% or < 6-7% respectively); however, these reports did not investigate the oldest-old population. Comprehensive geriatric assessment (CGA) and a patient-centered approach have been proven to improve the quality of care in the management of Type 2 Diabetes Mellitus (T2DM) in the older patients, but data regarding T2DM in patients with fragility fractures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 50 publications
(52 reference statements)
0
19
0
Order By: Relevance
“…Two studies 23,24 investigated length of hospital stay as an outcome although this was a secondary outcome in both studies. Paterni et al 24 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies 23,24 investigated length of hospital stay as an outcome although this was a secondary outcome in both studies. Paterni et al 24 .…”
Section: Resultsmentioning
confidence: 99%
“…These two studies may reflect that those with increased service utilisation may well have the greatest health needs, but they can also suggest where further focus on care is required. Paterni et al 24 . found that frail participants without optimal glycaemic control determined by HbA1c showed a four‐ to five‐fold higher mortality compared to robust participants, whilst no difference in mortality rate was found between robust and frail participants with strict glycaemic control (HbA1c < 48 mmol/mol).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not control all risk factors, such as smoking and other unknown confounders, which may potentially influence the findings. Although HbA1c is a reliable indicator of long-term glycemic control, providing a picture of patients’ average blood glucose levels during the previous two to three months, 31 conflicting results have been reported regarding mortality and postoperative complications after orthopedic procedures including hip fracture surgery. 32 , 33 Through this study, we aimed to compare the adverse outcomes following hip fracture surgery in DM and non-DM patients.…”
Section: Discussionmentioning
confidence: 99%